Characterization of peach tree crown by using high-resolution images from an unmanned aerial vehicle - Yue Mu; Yuichiro Fujii; Daisuke Takata; Bangyou Zheng; Koji Noshita; Kiyoshi Honda; Seishi Ninomiya; Wei Guo (Horticulture Research, 2018)
Precision horticulture: Peachy method for monitoring orchard growth A rapid automated system for monitoring peach tree growth had been developed that could replace laborious field measurements and enable farmers to manage their orchards more effectively. Knowing a tree’s crown width—the mass of branches and foliage growing outwards from its trunk—enables more effective spraying, machine harvesting, and assessment of trees’ growth. However, because peach trees have irregular shaped crowns, there is no rapid and reliable method for extracting this information. Wei Guo at the University of Tokyo and colleagues used unmanned aerial vehicles to photograph an orchard, then generated a digital surface model which enabled individual trees to be identified, and their crown widths and projection areas to be accurately calculated. This revealed that the trees grew faster during early summer compared to late summer, with wide variation between individual trees.